Effect of agriculture-nutrition education and extension services on early adoption and diffusion of biofortfied crops: The case of orange-fleshed sweetpotato in Kenya - Okello, J.J.; Muoki, Penina Ngusye; Kwikiriza, N.; Wambaya, J.; Heck, S. (2018)
Biofortification of crops as part of the effort to combat micronutrient deficiencies especially in developing countries gaining global recognition. Recent award of world food price to biofortification of staple crops has further energized efforts to promote the cultivation and consumption of biofortified crops. As part of the promotion efforts, some projects use intensive agriculture-nutrition education and extension to increase adoption of such crops by vulnerable households and their diffusion in local communities. This study used discrete choice regression analysis and data collected from households targeted by a project with one of the most intense agriculture-nutrition education and extension program to test the effect of such education and extension program on the adoption and diffusion of biofortfied crops. The study was conducted in western Kenya and involved 537 households with children under 5 years, a pregnant or lactating women. The study finds that intensive agriculture-nutrition education and extension programs adopted by some of the biofortification projects indeed increases the likelihood of adoption and diffusion of biofortified crops. It specifically finds that participation in events that offer practical education on the agronomy and preparation of foods from such crops, participation in mother-to-mother nutrition support platforms and nutrition-focused health talks affect adoption and diffusion of biofortified crops, but with varying degrees of importance. Among control factors, ability to conserve the planting material over dry period and household assets-endowments are important in both adoption and diffusion of biofortified crops. The paper discusses the implications of these findings.